STUDI HUBUNG SINGKAT PADA TRANSFORMATOR TEGANGAN TINGGI MENGGUNAKAN ETAP 16.0.0 - Julio Betran Simalango; Egy Wira indana; Muhammad Rizky Hidayah; Arwadi Sinuraya; Desman Jonto Sinaga (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Short-circuit fault is a dangerous condition in power systems because it produces very high currents. Transformers, as important equipment in high-voltage systems, must be analyzed to ensure safe operation during faults. This study aims to analyze short-circuit characteristics of a high-voltage transformer using ETAP 16.0.0.softwareShort-circuit fault is a dangerous condition in power systems because it produces very high currents. Transformers, as important equipment in high-voltage systems, must be analyzed to ensure safe operation during faults. This study aims to analyze short-circuit characteristics of a high-voltage transformer using ETAP 16.0.0 software.This research is expected to be used as a reference for designing protection systems for high-voltage equipment.